PENGGUNAAN FILTER AKTIF DENGAN PI CONTROLLER UNTUK MEREDAM HARMONISA PADA PEMBANGKIT LISTRIK TENAGA SOLAR CELL - Diki dwi aprisetiawan Diki; Istiyo Winarno; Belly Yan Dewantara (KURVATEK, 2021)
In an ideal electric power system, electrical energy is transmitted constantly both frequency and current. Because increasing power loads are more complex, especially non-linear loads, it will change the waveform and current spectrum to be distorted. The distorted waves and spectra in the current are due to the interaction between the sinusoidal wave system and other wave components known as harmonics. This study discusses changes in waves and spectrum in the PV mini-grid system by using active filters using PI control using a controlled rectifier load load with an ignition angle of 35 ° -180 ° so that the spectrum wave defect shape will be seen in non-linear loads that have an impact on equipment disturbances such as overheating increases losses and makes electronic devices fast. Active filter using PI control is based on a single-phase inverter with four control switches, the inverter will be connected in parallel with nonlinear loads. From the trial using Power Simulation (PSim) simulation software, it displays the simulation results with a spectrum of waves which is the application of active filter design. The simulation results show an improvement in waveform, spectrum graph and THD by installing active filters using PI control.